Online Sales and Bookkeeping with Improved Apps and Online Content - Kirana Ikhtiari; Muhammad Faisal AR Pelu; M. Muslim (Golden Ratio of Community Services and Dedication, 2021)
This community service activity aims to guide the community on making online sales and making business books using applications. The approach method offered to support community service program activities is a participatory method in which partners are directly involved in implementing actions from preparation to performance of these activities. The form of exercise is holding meetings in simple accounting bookkeeping training for businesses using applications and counseling about online sales. The type of output that will be generated based on the activity plan in community service is in the form of a module containing how to do simple accounting books for businesses using applications and how to make online sales by increasing online content and strategies for selling online to be able to increase sales income.